2006
DOI: 10.1002/mrd.20654
|View full text |Cite
|
Sign up to set email alerts
|

Donor cell differentiation, reprogramming, and cloning efficiency: Elusive or illusive correlation?

Abstract: Compared to other assisted reproductive technologies, mammalian nuclear transfer (NT) cloning is inefficient in generating viable offspring. It has been postulated that nuclear reprogramming and cloning efficiency can be increased by choosing less differentiated cell types as nuclear donors. This hypothesis is mainly supported by comparative mouse cloning experiments using early blastomeres, embryonic stem (ES) cells, and terminally differentiated somatic donor cells. We have re-evaluated these comparisons, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 74 publications
1
52
0
Order By: Relevance
“…More recently, iPSC have been generated from monkey (42), rat (43), and, while this manuscript was under review, miniature swine (44). This technology might be especially valuable in agriculturally important species for nuclear transfer experiments, as pluripotent cells might provide higher cloning efficiency and avoid the abnormalities and deaths associated with using differentiated somatic cells (45). In addition, it might be possible to establish gene targeting technologies with the ultimate goal of creating genetic models for human diseases in species where mouse models are inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, iPSC have been generated from monkey (42), rat (43), and, while this manuscript was under review, miniature swine (44). This technology might be especially valuable in agriculturally important species for nuclear transfer experiments, as pluripotent cells might provide higher cloning efficiency and avoid the abnormalities and deaths associated with using differentiated somatic cells (45). In addition, it might be possible to establish gene targeting technologies with the ultimate goal of creating genetic models for human diseases in species where mouse models are inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…We have learnt from mouse experiments that the easiest cells to reprogram are blastomeres from a morula; however, efficiency progressively declines when cells from the inner cell mass and tissue-specific cells are used (Gurdon and Melton, 2008;Hochedlinger and Jaenisch, 2006;Thuan et al, 2010;Wakamatsu, 2008). Side-by-side comparisons of different cell types showed that ESCs were more amenable to cloning than somatic fibroblasts (Rideout et al, 2000); and even among different somatic cell populations, the variations in cloning efficiency were significant (Oback, 2009;Oback and Wells, 2007). In amphibians, adult frogs were obtained when donor nuclei were isolated from blas-tomeres (Gurdon et al, 1958) and embryonic-intestinal cells (Gurdon and Uehlinger, 1966), but only tadpoles were produced using adult cells as donor nuclei (Gurdon et al, 1975;Laskey and Gurdon, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Cloning studies in different animal species have shown that the donor cell type is one of the most important factors determining the success of cloning [1,2]. Laboratory mouse strains provide the best models for this kind of study, because they allow rigorously controlled experiments using genetically defined animals.…”
Section: Introductionmentioning
confidence: 99%